KINERJA KEUANGAN SEBELUM DAN SESUDAH MERGER: STUDI KASUS DI INDONESIA, SWEDIA, DAN AMERIKA SERIKAT - Wardana, Wardana; Widiyati, Dian; Holiawati, Holiawati (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study examines pre- and post-merger financial performance across Indonesia, Sweden, and the United States, addressing inconsistent prior findings on merger impacts. The objective is to empirically test merger effects on profitability (ROE, ROA), liquidity (CR), solvency (CAR, DER), and activity (TATO, FAT) ratios using a five-year before-after (2014-2018 vs. 2019-2023) comparison. Employing a quantitative descriptive-comparative approach grounded in positivism, purposive sampling selected three cases: PT Bank Oke Indonesia Tbk (DNAR, Indonesia), Bristol Myers Squibb (BMSC, USA), and ÅF Pöyry AB (AFRY, Sweden), with secondary data from audited financial reports processed via SPSS 26. Instruments include standard financial ratios, descriptive statistics, Shapiro-Wilk normality tests, and paired sample t-tests. Results reveal no significant differences (all p > 0.05), indicating stable performance without merger-induced shifts. In conclusion, mergers primarily stabilize financial health across emerging and developed markets rather than drive improvements.